A History of the Journal of Conflict Resolution. (October 2017) - Russett, Bruce
This article examines the experience of this interdisciplinary journal dedicated to rigorous scientific research on the issues of war and peace. It opens with Journal of Conflict Resolution 's birth at the University of Michigan and then proceeds through its thirty-seven years at Yale and then to its period from 2009 to the present at the University of Maryland.